Shoulder position for shooting - Miller, S. (coachesinfo.com)
The problem is quite a simple one. Keeping the shoulder, elbow and wrist of the shooting arm in a line with the eyes and the basket is a common coaching point. To so this, however, requires turning the shoulders to bring the shoulder, elbow and wrist of the shooting arm into the line between the eyes and basket. This is because, when facing the basket, the shoulder of the shooting arm is to one side of the line between the eyes and basket. Turning the shoulders is not, in itself, a problem (and most shooters actually do so), but one problem that may arise is that for a right-handed player to attempt a shot while dribbling to the right (on the right-hand side of the court) requires the body to turn more (to the left) in order to face the hoop than if the same player was dribbling to the left on the left side of the court. This phenomenon can be seen at all standards. A good example in the NBA is John Crotty, a guard for the Utah Jazz, who is regarded as a good shooter. The knock-on effect is that players who turn their shoulders a lot can be deterred from shooting more easily when dribbling towards the end-line on the right side of the court for a right-handed shooter, and on the left side of the court for a left-handed shooter. The implication is the amount of shoulder turn should be minimised when teaching players to shoot.